Quranic Language Politeness Education in the Era of the Industrial Revolution 4.0 - Tengku, Silvana Sinar; Lubis, Syahron; Zein, Thyrhaya; Nurlela; Zulfan (Talenta Publisher, 2019)
This paper aims to introduce the modesty model of the qurani language as an alternative foundation of the politeness theories of language that have been taught so far. This model is important to be applied in the life of industrial revolution society 4.0. Fundamentally the industrial revolution 4.0 has caused changes in the way humans live, think, and interact in establishing relationships with one another. In turn this era has disrupted various human activities. These include language activities which are a form of social interaction. The phenomenon of impoliteness, harassment (bullying), and verbal violence is increasingly massive in the real world. Even the industrial revolution 4.0 which provides easy internet access and advances in information technology has also led to an increase in the phenomenon of hate speech, the dissemination of hoaxes and cyber bullying that can threaten social harmony and the unity of the multicultural Indonesian nation. Therefore it is necessary to develop a polite language education model based on religious teachings.